2017
DOI: 10.1177/1591019917703784
|View full text |Cite
|
Sign up to set email alerts
|

MRI findings in lumbar spine following O2–O3 chemiodiscolysis: A long-term follow-up

Abstract: Intradiscal O2–O3 injections are conventionally used as a minimally invasive treatment for lumbar disc herniation in patients not responding to conservative treatments. The aim of the present study is to report data of long-term imaging follow-up (3 years) of patients treated with intradiscal O2–O3 lumbar chemiodiscolysis. We evaluated the changes of disc volume and the modifications in disc appearance (in terms of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The grading system for bone marrow changes near the endplate was implemented by Modic et al who gave MRI definitions of such alterations [8,20,29]. The etiopathogenesis of Modic changes type I is still a matter of debate [20,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The grading system for bone marrow changes near the endplate was implemented by Modic et al who gave MRI definitions of such alterations [8,20,29]. The etiopathogenesis of Modic changes type I is still a matter of debate [20,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Similarly, a significant volume reduction was detected in the 6-month assessment of 283 patients with CT.[ 19 ] Muto et al showed a 63% reduction in disk volume at month 18 while Bruno et al reported a significant volume reduction at year 3. [ 12 , 20 ] Due to the design of our study, evaluation of the disc volumes could not be done for the patients in our study but our serendipitous clinical observations confirmed this effect.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, pain relief can be accompanied by a shrinkage or disappearance of the bulging herniated disc responsible for nerve root compression, which has been evaluated in studies via MRI checking with no acceleration of the disc degeneration process in long-term follow-up. 17 21 …”
Section: Discussionmentioning
confidence: 99%